Correlation between Total Lymphocyte Count, C Reactive Protein, and Neutrophil Lymphocyte Ratio Levels with Gastrointestinal Manifestations in Covid-19 Patients Treated at Ulin Hospital, Banjarmasin - Sanjaya, Bernadet Maria; Soefyani, Achmad; Fajari, Nanang Miftah; Cahyawati, Wiwit Agung Sri Nur; Rudiansyah, Mohammad (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Coronavirus disease can affect the digestive system and cause gastrointestinal manifestations. The increase in C-reactive protein (CRP) correlates with the severity of the disease. The neutrophil-to-lymphocyte ratio (NLR) is a useful prognostic factor in the early screening of patients with COVID-19. A low lymphocyte count can also predict gastrointestinal involvement. AIM: This study aims to determine the correlation between TLC, CRP, and NLR levels on gastrointestinal manifestations in COVID-19 patients treated at Ulin General Hospital, Banjarmasin. METHODS: This study used a cross-sectional design. Data were taken consecutively using the medical records of confirmed COVID-19 patients with gastrointestinal manifestations. The number of subjects in this study was 88 patients. RESULTS: A decrease in TLC levels (<1740 g/dL) was not proven to have a significant correlation with gastrointestinal manifestations in COVID-19 patients (p = 0.176). Increased levels of CRP (>48 mg/L) had a significant correlation by 5.71 times compared to subjects who did not experience increased CRP (p < 0.00001). Increased levels of the NLR (>6 mg/L) had a significant correlation by 2.82 times compared to subjects who did not experience an increase in NLR (p = 0.032). CONCLISION: An increase in CRP levels >48 mg/L and levels of NLR >6, respectively, allowed the subject to experience gastrointestinal symptoms by 5.71 times and 2.82 times when infected with COVID-19, while a decrease in total lymphocyte count <1740 was not proven to have a significant correlation with gastrointestinal manifestations.